Memristor‐transistor hybrid ternary content addressable memory using ternary memristive memory cell - Masoodur Rahman Khan; ABM Harun‐ur Rashid (IET Circuits, Devices and Systems)
Abstract A memristor‐transistor hybrid ternary content addressable memory (MTCAM) with a memristor‐based ternary memory cell is proposed. New emerging devices like memristors have recently been explored to overcome the limitations of CMOS‐based memory circuits. The memristor is used as a binary memory cell in these MTCAM designs to replace a CMOS‐based memory cell. This proposed design used a memristor as a ternary memory cell by exploiting its variable resistance characteristics. The associated wiring is reduced almost by a factor of 2 as a ternary cell is used instead of two binary cells. Area efficiency is further enhanced as the MTCAM cell is comprised of two transistors and two memristors (2T2M). A segmentation technique of match line along with a robust write/search operation method is presented to enhance the search speed of the proposed MTCAM. Simulation based on a mathematical model of memristor is presented and analysed using 65 nm TSMC MOS model parameters. Corner simulations and Monte Carlo simulations are carried out to substantiate the robustness of the design against process variation. Simulation results show the worst search delay of 0.75 ns and the energy/bit/search of 0.866 fJ for the 128 × 128 bit MTCAM.